Adoption of enclosure and windbreaks to prevent the degradation of the cooling performance for a natural draft dry cooling tower under crosswind conditions. (1st December 2016) - Wang, Weiliang; Zhang, Hai; Li, Zheng; Lv, Junfu; Ni, Weidou; Li, Yongsheng
Abstract: Crosswind degrades the cooling performance of a natural draft dry cooling tower (NDDCT) by affecting the air flow field at the inlet and outlet and inducing complex vortices inside and outside the tower. The distribution of the vortices along the flow streams is found to be a key factor for the ventilation rate. The parameter of flow loss factor (FLF) is proposed to quantitatively identify the effect of the vortices and unbalanced flow on the ventilation rate. Approaches of the installations of windbreaks and enclosure on the cooling performance of the NDDCT are numerically studied. It is found that both approaches can individually reduce the size of the inner wall vortex, improving the flow field characteristics. However, they have different strengths in breaking up the side low pressure areas and reducing the swirling intensity of the mainstream vortices. Results show that the approaches of windbreaks and enclosure can effectively prevent the degradation of the cooling performance for the NDDCT in a wide crosswind velocity range, and their combination could nearly eliminates the negative effect of the crosswind. Highlights: Approaches to prevent the cooling performance degradation for a NDDCT are studied. Flow loss factor (FLF) is proposed to indicate the flow field effect on ventilation. Vortices affect the ventilation rate via affecting the FLF in along the flow stream. An enclosure achieves a similar performance to windbreaks. A combination of the two approaches eliminates the degradation effect of crosswind.